Cooperation of the Central Asian countries with the regional office of the United Nations High Commissioner for Human Rights - Rajabov А.С.; Sarsembayev М.А. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2024)
This article analyzes the issues of cooperation between Central Asian countries and the regional office of the United Nations High Commissioner for Human Rights. The establishment of a Regional office in Bishkek (Kyrgyzstan) in 2008 and its activities, which cover Kazakhstan, Tajikistan, Kyrgyzstan, Turkmenistan, and Uzbekistan, are considered. The purpose, main directions and ideas of scientific research are formulated in the following form. It highlights the specifics of the Regional Office’s cooperation with the countries of the region on human rights and freedoms. The mandate of the Regional Office allows interaction with Governments, international organizations, and representatives of civil society, which contributes to the development and implementation of programs for the protection of human rights and freedoms. The scientific significance of this work is evident in the fact that it shows how the process of strengthening human rights protection in the region took place through educational programs, trainings, and seminars. The practical significance lies in the fact that this article presents successful practices of cooperation between representative offices that were established in various cities of the studied region. The research methodology includes the method of comparative legal analysis, the logical method and the method of scientific forecasting. The main results and conclusions include: the need to organize the fight against corruption crimes in order to better respect human rights; the presence of a positive impact of the Regional Office on improving the effectiveness of the work of national human rights institutions; improving the mechanism for the observance and protection of human rights through the formulation of legislative and convention recommendations and proposals in the article. The value of the convention and legislative recommendations is reduced to the need to establish a Central Asian Court of Human Rights based on the principles of the European Court of Human Rights. The practical significance of the results of the work is that the decisions of the Central Asian Court of Human Rights should become binding for each State in the region and its courts, which would raise the level of human rights protection in the region.